2012
DOI: 10.1021/jo3004277
|View full text |Cite
|
Sign up to set email alerts
|

Added-Metal-Free Catalytic Nucleophilic Addition of Grignard Reagents to Ketones

Abstract: On the basis of the investigation of the combinational effect of quaternary ammonium salts and organic bases, an added-metal-free catalytic system for nucleophilic addition reactions of a variety of Grignard reagents to diverse ketones in THF solvent has been developed to produce tertiary alcohols in good to excellent yields. By using tetrabutylammonium chloride (NBu(4)Cl) as a catalyst and diglyme (DGDE) as an additive, this system strongly enhances the efficiency of addition at the expense of enolization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 54 publications
3
16
1
Order By: Relevance
“…Early examples of these additives include lanthanide halides, such as CeCl 3 and LaCl 3 23. Very recently, the combination of diglyme and a catalytic amount of Bu 4 NCl has been reported to enhance the efficiency of the addition of several types of Grignard reagents to compound 20 c to give the desired adducts in high yields 24. However, in our case, this combination did not work well, and the yield of compound 21 c was not improved.…”
Section: Resultscontrasting
confidence: 60%
“…Early examples of these additives include lanthanide halides, such as CeCl 3 and LaCl 3 23. Very recently, the combination of diglyme and a catalytic amount of Bu 4 NCl has been reported to enhance the efficiency of the addition of several types of Grignard reagents to compound 20 c to give the desired adducts in high yields 24. However, in our case, this combination did not work well, and the yield of compound 21 c was not improved.…”
Section: Resultscontrasting
confidence: 60%
“…Supporting this, addition of substoichiometric TMEDA, which is known to break up RMgCl aggregates, dramatically increased the observed reactivity under the “all chloride” conditions (entry 3). 35 Taken together, these results support the hypothesis that this catalytic system is capable of direct Si–Cl bond activation. Studies to further elucidate the mechanism of this transformation are currently underway.…”
supporting
confidence: 72%
“…Germane to this work, Song has recently shown that catalytic amounts of ammonium salt NBu 4 Cl in THF solutions of Grignard reagents can greatly enhance the chemoselectivity of addition reactions, minimizing formation of enolization and reduction products. [14] The authors proposed that substoichiometric amounts of the salt can shift the position of the Schlenk equilibrium of Grignard reagents to form dinuclear R 2 Mg·MgX 2 species which would favor addition. Since a main component in the eutectic mixtures employed in this work is an ammonium salt, a related activation effect can be operative.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly ethynylmagnesium bromide reacts with 1 a, affording 2 f in a 77 and a 72 % yield depending on the eutectic mixture employed (entries 11 and 12). [14] The authors proposed that substoichiometric amounts of the salt can shift the position of the Schlenk equilibrium of Grignard reagents to form dinuclear R 2 Mg·MgX 2 species which would favor addition. [4c] Theoretical and experimental studies monitoring the addition reactions of carbonyl compounds by Grignard reagents, using neat water as a solvent, have shown that while for allyl Grignard reagents additions take place at a comparable rate to those of the competing hydrolysis processes, [10] alkyl analogs, such as BuMgCl, are much more kinetically retarded (addition reaction is up to 10 5 times slower), [13] and therefore protonation occurs preferentially, yielding only trace amounts of addition products.…”
mentioning
confidence: 99%